Implementasi Pembelajaran Bahasa Arab dengan Pendekatan Sing a Song di Pondok Pesantren Sahabat Quran El-Yamin Pacitan - Ajib Pangestu; Sanjaka Yekti (YASIN, 2026)
Arabic language learning at Sahabat Qur’an El Yamin Islamic Boarding School in Pacitan still faces obstacles in the form of low student motivation and vocabulary mastery, mainly because of the dominance of lecture and memorization methods, which tend to make learning perceived as difficult and boring. This study aimed to describe the implementation of the Sing a Song approach, analyze its impact on learning motivation and participation, and identify obstacles and improvement strategies in the Islamic boarding school context. This study used a qualitative approach with a case study design, involving teachers, students, and Islamic boarding school administrators as informants. Data were collected through interviews, observation, and documentation, and were then analyzed using the Miles, Huberman, and Saldana model. The results showed that the Sing a Song approach was able to increase motivation, participation, and Arabic vocabulary mastery. However, its implementation still faced obstacles in the form of some students’ dependence on the song format and a lack of understanding of vocabulary meanings. These findings confirm that the Sing a Song approach is effective as a creative learning strategy in Islamic boarding schools, but it needs to be combined with grammatical explanation and communicative practice so that Arabic language understanding becomes more comprehensive. The implications of this study indicate that this approach can be adopted in the development of music-based Arabic language modules and curricula in other Islamic educational institutions.